The Influence of Transformational Leadership Style and Work Discipline on Employee Performance Through Work Motivation as a Intervening Variable Among BAPPERIDA Staff in Serang City - Helmi Muhammad Ilyasa; Wahyu Wiguna; Muhammad Suparmoko (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Employee performance was an important factor in the success of public sector organizations, particularly Bapperida Kota Serang, which played a strategic role in regional development planning and innovation. Employee performance was influenced by various organizational factors, including transformational leadership style, work discipline, and work motivation. This study aimed to analyze the influence of transformational leadership style and work discipline on employee performance, both directly and indirectly through work motivation as a mediating variable at Bapperida Kota Serang. This study employed a quantitative approach using a survey method. Data were collected from 100 employees of Bapperida Kota Serang and were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that work discipline and work motivation had a positive and significant effect on employee performance. Transformational leadership had a significant effect on work motivation but did not have a direct effect on employee performance. Work motivation mediated the relationship between transformational leadership and employee performance but did not mediate the relationship between work discipline and employee performance. This study concluded that work motivation was a key variable in improving employee performance at Bapperida Kota Serang. Therefore, efforts to enhance employee performance were more effective when they focused on strengthening work motivation, supported by participative transformational leadership and adaptive work discipline oriented toward psychological support.